Photovoltaic solar energy in brazil and the contribution of Federal Institute of Rio Grande do Norte (IFRN) - Wanderley, Augusto Cesar Fialho (2015)
Photovoltaic solar energy is presented as a promising source for Brazil, considering that most of the Brazilian territory is located near the equator, which implies days with the highest number of hours of sunlight. The participation of this energy source in the Brazilian energy matrix corresponds to only 0.01% of installed capacity. Important actions are being made to increase this participation: R & D programs of electric utilities, regulation of distributed microgeneration and minigeneration, energy auctions of the Federal Government and publication of technical standards by the Brazilian Association of Technical Standards (ABNT). This paper presents the initiatives for the implementation of photovoltaic solar energy in Brazil, the prospects for its consolidation as a source of energy, and the contribution of the Federal Institute of Rio Grande do Norte (IFRN) for this scenario. The analysis of the economic and financial viability of photovoltaic solar plant installed at the Rectory of IFRN and the consequent reduction of expenses with electricity are also presented.